Kurikulum Pendidikan dan Pelatihan di Badan Pengembangan Sumber Daya Manusia Sumatera Utara - Lathifatun Nisa Hutabarat; Lilis Juliyanty Marbun (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
The curriculum for education and training is a plan, objectives, content, and learning approach that is structured to direct the education process in order to achieve certain abilities in students or training participants. In a formal education environment, the curriculum serves as the main guide for institutions and educators in setting learning targets, compiling teaching materials, choosing teaching techniques, and assessing educational outcomes. On the other hand, in training programs, the curriculum focuses more on achieving specific skills needed in the work environment, with materials and strategies adapted to the needs and character of the participants. The main elements of the curriculum include objectives, content, methods, and evaluation, all of which must reinforce each other to ensure the achievement of the desired results, both in cognitive, affective, and psychomotor aspects. The process of developing an education and training curriculum requires needs analysis,es goal setting, content development, selection of learning experiences, and preparation of appropriate evaluation instruments. Therefore, the curriculum in education and training not only functions as a tool for planning and organizing learning, but also as a driver of change and improvement in the quality of human resources that are responsive e, and needs in the world of work.